Review—Device Assessment of Electrically Active Defects in High-Mobility Materials. (28th January 2016) - Claeys, C.; Simoen, E.; Eneman, G.; Ni, K.; Hikavyy, A.; Loo, R.; Gupta, S.; Merckling, C.; Alian, A.; Caymax, M.
Abstract : The stringent device performance specifications of advanced scaled down technologies necessitates the implementation of high mobility substrates such as SiGe, Strained Si (sSi), Ge, sGe and/or III-V materials like GaAs, InGaAs. The control of the stress-induced defects remains a key challenge. Simple device structures such as capacitors, diodes and transistors are used to assess the electrical activity of extended defects (dislocations; antiphase boundaries; …) in high-mobility channel materials. Beside junction current analyses and lifetime studies, also the use of low-frequency noise characterization is reported. Special case studies are discussed to illustrate the used methodology. The potential of TCAD studies to better understand the electrical defect activity is also briefly addressed.